1996
DOI: 10.1007/bf00036471
|View full text |Cite
|
Sign up to set email alerts
|

An empirical model for sediment resuspension in shallow lakes

Abstract: Suspended solids concentrations were measured at routine 2-3 week intervals and on additional windy days for at least one year in each of seven shallow (mean depth < 2 m) South Island, New Zealand lakes . Surface wave characteristics were estimated from water depths and local meteorological data using a shallow-water wave forecasting model for fetch-limited waves . Bottom shear stresses were computed from surface wave characteristics for the sampling stations and for a hypothetical lake-average station . The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(96 citation statements)
references
References 45 publications
3
91
0
Order By: Relevance
“…This change can be expected to increase exposure of bottom sediments to the erosive effects of wind, leading to sediment resuspension and reduced light availability (Hamilton & Mitchell 1996;Scheffer 1998). These conditions may favour growth of C. raciborskii, with its capacity to grow well at low irradiance (Padisák & Reynolds 1998).…”
Section: Resultsmentioning
confidence: 99%
“…This change can be expected to increase exposure of bottom sediments to the erosive effects of wind, leading to sediment resuspension and reduced light availability (Hamilton & Mitchell 1996;Scheffer 1998). These conditions may favour growth of C. raciborskii, with its capacity to grow well at low irradiance (Padisák & Reynolds 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Wave damping due to vegetation in lakes has been even less investigated than in the ocean, especially with regard to field measurements, although its indirect effects on the light climate are well known (e.g., Hamilton and Mitchell 1996). However, the damping of waves over submerged vegetation has been analyzed in the laboratory (Houwing et al 2002).…”
Section: Previous Studiesmentioning
confidence: 99%
“…These vegetated belts act as buffer zones protecting nearshore structures and ecosystems (e.g., Asano et al 1992). In shallow lakes and wetlands, submerged and emergent vegetation are known to reduce resuspension of bottom sediments by decreasing the wave energy (Hamilton and Mitchell 1996;Horppila and Nurminen 2001;Houwing et al 2002). This reduction has several ecological effects as light climate is enhanced and internal loading of sediment-bound nutrients is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Carp can physically disturb and resuspend bottom sediments through feeding behavior (King and Hunt, 1967). Subsequently, resuspended sediments can thereby diminish light availability, which induces significant decrease of aquatic macrophytes in the water body (Hamilton and Mitchell, 1997;Miller and Crowl, 2006). Lougheed et al (1988) showed that water turbidity and nutrient loading increased proportionally with the biomass of spawning carp in experimental enclosures.…”
Section: Introductionmentioning
confidence: 99%